Pharmacoepidemiological Study of Uterine Fibroids in Indore City - NEELESH NAYAK; ALOK SONI; MITHUN SINGH RAJPUT; VINEET MATHUR; VEENA NAIR (International Journal of Pharma and Bio Sciences, 2010)
Uterine fibroids (leiomyomas) are common, benign, noncancerous tumors of smooth muscle cells and fibrous connective tissue that develop within the myometrium of the uterus and are estrogen dependent. The aim of this study is to evaluate the approach of gynecologists to the diagnosis and management of uterine fibroids in Indore city. A questionnaire to be self administered was prepared and presented to gynecologists of Indore city. The data was obtained and analyzed to present the result. It was concluded that uterine tumor is seen mostly in females of age group 14-60 and etiology differ in various individuals. View of gynecologists of Indore city represents that hysterectomy is beneficial to overall health and wellness of women bearing uterine fibroids.